WOOD PROCESSING TECHNIQUES AS A MEANS OF CREATION OF LAND ART OBJECTS - Halchynska, O. S.; Protsyk, B. O.; Krichlow, K. V.; Navolska, L. V. (Art and Design, 2021)
The purpose of the article is to study the land art objects created from the wood by various techniques used by the artists. To achieve the purpose, the following tasks have been identified and solved: the analysis of means of wood processing used by the artists to create the works of land art has been performed; the types of materials used to create installations have been determined; modern wood processing techniques and their characteristic features introduced in the land art objects have been studied. Methodology. The system approach, methods of typological, comparative-historical, reconstructive, structural-functional analysis, etc. are used. Results of the research. The study of wood processing techniques used by the artists of land art in their works has been conducted. The special decorative significance of wood processing techniques during the realization of the art object and their influence on the concept of the work have been determined. It has been found that the main trends in modern art are the environmental friendliness of materials used by the artists of land art, the use and restoration of ethnographic techniques and methods of creating art objects, but giving the work its own semantic component, often environmental one. The scientific novelty is to determine the author`s artistic techniques and approaches used for the creation of objects of land art in wood processing techniques, to develop the typologies of objects of land art from wood, as well as to determine the impact of traditional wood processing industries on the work of the artists of land art of our days. The practical significance lies in the fact that the materials presented in the article, their analysis and generalization can be used in research on the development of land art in Ukraine and the world, as well as for further implementation in the author`s art projects.